Análise de vibrações em pisos mistos de aço e concreto induzidas por atividades rítmicas - Almeida, Mateus Madureira de (2021)
The growing use of composite systems floors of steel and concrete in open spans design that aim to increase use flexibility of buildings using large open spaces, has stimulates the conception of composite systems floors in formats leave them more sensitive to vibratory effects and this way, meet human’s comfort criteria become increasingly important already in the early stages of structures design. The acceptance criteria of the national standards, based only control of fundamental frequency, lead to insufficient verifications, due the fact that real influence of vibrations induced by human’s activities in human comfort are related with peak accelerations. Within this context, this work present knowledge about dynamic behaviour of composite systems floors of steel and concrete for understanding of vibrations effects in the human comfort, together with of clustering of analytical procedures to calculate the fundamental frequency and acceleration of composite floors, procedures for numerical modelling, humans comfort criteria of vibrations induced by human’s activities, besides of, detailed examples using analytical procedures and application of human comfort criteria in composite floors design. Using analytical processes and numerical models for determine modal properties of 36 composite floors, after evaluating them based human comfort criteria of national standards and reputed international guides, was possible conclude that national standards need updated, as the results showed divers floors that not fit in criteria of reputed international guides design, when verified against in national standards, they would pass in the criteria of national codes.